2003
DOI: 10.1093/sleep/26.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hypocretin-1 (Orexin-A) Levels in the Cerebrospinal Fluid of Patients with Myotonic Dystrophy and Excessive Daytime Sleepiness

Abstract: A dysfunction of the hypothalamic hypocretin system may mediate sleepiness and abnormal Multiple Sleep Latency Test results in patients with myotonic dystrophy type 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(61 citation statements)
references
References 38 publications
3
55
2
1
Order By: Relevance
“…Results of the present study differ from a previous study of six patients with DM1, in which one patient had Hcrt-1 levels below110 pg/mL in CSF, and three patients had Hcrt-1 levels between 110 and 200 pg/mL, 25 a range that is intermediate between levels observed in normal individuals and patients with narcolepsy. 23 By contrast, only 3 of 38 patients with DM1 in the current study, as compared to 2 of 33 controls, had levels in this intermediate range.…”
Section: Analysis Of Hcrt Receptor (Hcrtr) Splicingcontrasting
confidence: 99%
See 2 more Smart Citations
“…Results of the present study differ from a previous study of six patients with DM1, in which one patient had Hcrt-1 levels below110 pg/mL in CSF, and three patients had Hcrt-1 levels between 110 and 200 pg/mL, 25 a range that is intermediate between levels observed in normal individuals and patients with narcolepsy. 23 By contrast, only 3 of 38 patients with DM1 in the current study, as compared to 2 of 33 controls, had levels in this intermediate range.…”
Section: Analysis Of Hcrt Receptor (Hcrtr) Splicingcontrasting
confidence: 99%
“…23 Hereditary narcolepsy in dogs is caused by mutations that affect splicing in the hypocretin receptor 2 (HcrtR2) gene. 24 Recently it was reported that Hcrt-1 was reduced in CSF in patients with DM1 25 and that sleep onset REM, similar to that observed in narcolepsy, was observed in patients with DM1. 15,16 To determine if DM1 is associated with abnormal Hcrt-1 action, we carried out a prospective study of CSF Hcrt-1 in patients with DM1 who did or did not have EDS.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…One report documented abnormal protein content in a subset of patients with DM1, 43 the significance of which is unclear. More recently, Martinez-Rodriguez et al 68 reported decreased orexin-A levels in the cerebrospinal fluid of 3 of 9 patients with DM1 affected by excessive daytime sleepiness, thus suggesting analogies with the mechanisms involved in narcolepsy.…”
Section: Global Intelligencementioning
confidence: 98%
“…There is evidence to suggest complex, widespread malfunction of circadian and ultradian timing system, including neuroendocrine abnormalities in sleep. The patients complaining of excessive daytime sleepiness, with 39% to 77% of patients reporting, often require, in addition to measures to correct SDB, stimulant medication [37].…”
Section: Muscle Fiber Diseasementioning
confidence: 99%